The effect of the number of turns on the thermal resistance of pulsation heat pipes - Кравец, Владимир Юрьевич; Алексеик, Евгений Сергеевич; Аполлонина, Александра Юрьевна (Eastern-European Journal of Enterprise Technologies, 2012)
This article represents an overview of investigation of effect of number of turns on thermal resistance of pulsation heat pipes. Experimental setup for investigation of this effect, a routine of experiment is described. The characteristics of heat transfer processes that occur when pulsation heat pipe are working. The results of investigation are presented